Cybersecurity Risk Discussion with Relevant Laws (International Journal of Scientific Research in Science and Technology, 2024)
In the context of post Covid 19 pandemic, This paper outlines What are Cybersecurity risks? For online transactions? And What are suggestions for Protecting consumer interests in online transactions? By using analysis, experiences, observations, practical situation with cases studies of our country-Vietnam, and also use qualitative, analysis, synthesis research methods, this study suggest that When detecting that the account has an abnormality or mistakenly transferred or received, consumers need to contact the bank directly to solve it, do not bring it online to inquire, and do not send the OTP password to any individual request. Currently, most banks use Smart OTP, biometric authentication..., customers should also switch to this method, limit the use of receiving OTP passwords via SMS to avoid being cheated. Second, to prevent online risks clients need Not to provide personal information, bank account, OTP password, Internet banking and mobile banking username and password for strangers.